Rapid Growth of Dermatofibrosarcoma Protuberans Associated with Bilateral Adrenalectomy for Cushing's Syndrome - Sadanori Furudate; Taku Fujimura; Akira Hashimoto; Setsuya Aiba (Karger Publishers, 2011)
We describe a 50-year-old Japanese patient with dermatofibrosarcoma protuberans (DFSP) rapidly growing after bilateral adrenalectomy for Cushing's syndrome that reduced the serum level of cortisol from 17.1 to 0.8 mg/dl. It is known that glucocorticoids decrease the transcriptions of the COL1A1 gene and the PDGFB gene, which is under the direct control of the COL1A1 gene in most DFSP. Therefore, the hypersecretion of glucocorticoids in Cushing's syndrome might suppress the development of DFSP. To the best of our knowledge, this is the first case of rapid growth of DFSP that may be associated with bilateral adrenalectomy for Cushing's syndrome.